PENARAPAN KETENTUAN PIDANA TERHADAP PELAKU EKSPLOITASI PENYANDANG DISABILITAS DI KOTA PEKANBARU - Kurniawan, Ikhsan; Firdaus, Emilda; R, Mukhlis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Persons with disabilities are a diverse group of people, including persons with disabilities who have physical disabilities, mental disabilities or a combination of physical and mental disabilities. many people with disabilities are exploited such as busking and begging. However, in the effort to protect the rights of persons with disabilities that are free from discrimination and exploitation, there are still many problems in giving punishment to people who exploit persons with disabilities. The problems in this thesis, namely: First, How is the application of criminal provisions against the exploitation of persons with disabilities in Pekanbaru City? Second, what are the obstacles in enforcing criminal sanctions and the government's efforts to minimize exploitation of persons with disabilities in Pekanbaru City?This type of research can be classified in the type of sociological juridical research. This research was conducted in Pekanbaru City, while the sample population was all parties related to the problems examined in this study, the data sources used, primary data and secondary data, data collection techniques in this study by interview, observation and literature study.From the research, there are two things that can be concluded. First, Law Enforcement conducted by the Pekanbaru City Police against the exploits of persons with disabilities has so far never been enforced. This is because there are no complaints from victims or injured parties in this case. Secondly, the obstacles in the eradication of exploitation perpetrators are the lack of coordination of the police with other agencies such as the Satpol PP and the Pekanbaru City Social Service and the efforts made by the Pekanbaru City Police Criminal Investigation to minimize the exploitation of persons with disabilities including socializing and educating persons with disabilities regarding Law No. 8 of 2016 concerning Persons with Disabilities.Keywords: Explotation, Persons with Disabilities, Pekanbaru City,